Sex-differential genetic effect of phosphodiesterase 4D (PDE4D) on carotid atherosclerosis - Guo Yuh-Cherng; Lin Hsiu-Fen; Liao Yi-Chu; Yu Ming-Lung; Liu Ching-Kuan; Juo Suh-Hang (BMC, 2010)
Abstract Background The phosphodiesterase 4D (PDE4D) gene was reported as a susceptibility gene to stroke. The genetic effect might be attributed to its role in modulating the atherogenic process in the carotid arteries. Using carotid intima-media thickness (IMT) and plaque index as phenotypes, the present study sought to determine the influence of this gene on subclinical atherosclerosis. Methods Carotid ultrasonography was performed on 1013 stroke-free subjects who participated in the health screening programs (age 52.6 ± 12.2; 47.6% men). Genotype distribution was compared among the high-risk (plaque index ≥ 4), low-risk (index = 1-3), and reference (index = 0) groups. We analyzed continuous IMT data and further dichotomized IMT data using mean plus one standard deviation as the cutoff level. Because the plaque prevalence and IMT values displayed a notable difference between men and women, we carried out sex-specific analyses in addition to analyzing the overall data. Rs702553 at the PDE4D gene was selected because it conferred a risk for young stroke in our previous report. Previous young stroke data (190 cases and 211 controls) with an additional 532 control subjects without ultrasonic data were shown as a cross-validation for the genetic effect. Results In the overall analyses, the rare homozygote of rs702553 led to an OR of 3.1 (p = 0.034) for a plaque index ≥ 4. When subjects were stratified by sex, the genetic effect was only evident in men but not in women. Comparing male subjects with plaque index ≥ 4 and those with plaque index = 0, the TT genotype was over-represented (27.6% vs. 13.4%, p = 0.008). For dichotomized IMT data in men, the TT genotype had an OR of 2.1 (p = 0.032) for a thicker IMT at the common carotid artery compared with the (AA + AT) genotypes. In women, neither IMT nor plaque index was associated with rs702553. Similarly, SNP rs702553 was only significant in young stroke men (OR = 1.8, p = 0.025) but not in women (p = 0.27). Conclusions The present study demonstrates a sex-differential effect of PDE4D on IMT, plaque index and stroke, which highlights its influence on various aspects of atherogenesis.